The Effectiveness of Booklet Kearifan Lokal Tradisi Pengunduhan Sarang Burung Walet di Kebumen with PBL to Empower Analytical Thinking Skills - Putri, Najwa Salma Azizka Yusuf; Suciati*, Suciati; Silvita, Silvita; Prasetyo, Opik; Rachman, Hening Triandika (Universitas Syiah Kuala, 2025)
Students' lack of understanding of local wisdom and teachers' inability to integrate it into science lessons has resulted in students being less trained in problem solving, which in turn has led to underdeveloped analytical thinking skills (ATS). This study aims to: determine the effectiveness of using the local wisdom booklet of tradisi pengunduhan sarang burung walet (TPSBW) in Kebumen with the problem based learning (PBL) model in empowering ATS in seventh grade students in science subjects. The population in this study were all seventh grade students of SMP N 9 Surakarta in the 2024/2025 academic year. This type of research is quantitative with a quasi-experimental method. The sampling technique used cluster random sampling so that class VII H was obtained as the experimental class and class VII G as the control class. The research design used was pretest posttest control group. The data collection technique used a test method in the form of multiple choice questions. The research procedure includes, pretest, giving treatment by applying the local wisdom booklet of TPSBW in Kebumen with the PBL model in the experimental class and the PBL model alone in the control class, and posttest. The test was given to measure students' ATS. The results of this study are the application of the local wisdom booklet of TPSBW in Kebumen with the PBL model is effective in empowering students' ATS with a significance value (0.000 0.05). The average ATS in the experimental class increased by 18.70 points